Efficacy of a bacillus subtilis probiotic on growth performance and intestinal morphology of broiler chickens - Girish, Channarayapatna K.; Loh, Teck Chwen; Payne, R. L. (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
Effects of feeding probiotic (Bacillus subtilis; BS) or antibiotic growth promoter (AGP) alone or in combination on growth performance and intestinal morphology of broilers was studied. A total of 480 day-old male Cobb-400 broilers were grouped into 4 treatments and fed different diets: (1) corn-soybean meal based control (C), (2) C+AGP (100 ppm of oxytetracyclin and neomycin), (3) C+BS (500 g/T) and (4) C+BS+AGP. At day 42, feeding BS or AGP alone numerically improved body weight gain (BWG) of broilers compared with control whereas the combination of BS+AGP resulted in higher BWG indicating a synergistic effect. Feed conversion ratio improved (P≤0.05) when broilers were fed BS, or BS+AGP diets compared with C diet. Significant increase in duodenal villus height was observed when broilers were fed BS or AGP alone compared with those fed C diet. Feeding BS or BS+AGP diet increased (P≤0.05) the VH of jejnum and ileum compared with C diet, whereas VH was reduced in ileum of broilers fed AGP diet.These results indicate that BS can be a viable alternative or synergistic partner to AGP.